2016
DOI: 10.1038/srep29981
|View full text |Cite
|
Sign up to set email alerts
|

Seismic evidence for flow in the hydrated mantle wedge of the Ryukyu subduction zone

Abstract: It is widely accepted that water-rich serpentinite domains are commonly present in the mantle above shallow subducting slabs and play key roles in controlling the geochemical cycling and physical properties of subduction zones. Thermal and petrological models show the dominant serpentine mineral is antigorite. However, there is no good consensus on the amount, distribution and alignment of this mineral. Seismic velocities are commonly used to identify antigorite-rich domains, but antigorite is highly-anisotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 58 publications
(159 reference statements)
0
22
0
Order By: Relevance
“…Recent study indicated that serpentine should exhibit strong anisotropy and that its V p / V s varies widely (Nagaya et al, ). Active source surveys also suggest the anisotropy of the serpentinized layer at the top of the Nazca Plate (Contreras‐Reyes et al, ); however, the degree of anisotropy is small (<2%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study indicated that serpentine should exhibit strong anisotropy and that its V p / V s varies widely (Nagaya et al, ). Active source surveys also suggest the anisotropy of the serpentinized layer at the top of the Nazca Plate (Contreras‐Reyes et al, ); however, the degree of anisotropy is small (<2%).…”
Section: Resultsmentioning
confidence: 99%
“…Active source surveys also suggest the anisotropy of the serpentinized layer at the top of the Nazca Plate (Contreras‐Reyes et al, ); however, the degree of anisotropy is small (<2%). This difference might be explained by several situations: (1) differences in the degree of serpentinization, (2) variations in the incidence between the raypath and the (001) planes of the antigorite (Nagaya et al, ), and (3) differences in the homogeneity of the (001) plane orientation of the antigorite. Since our tomographic study assumes an isotropic model, structural studies with anisotropic information will be needed to reconcile these results.…”
Section: Resultsmentioning
confidence: 99%
“…Lynner and Long, 2014). The source of this trenchparallel seismic anisotropy was proposed as: (1) the trenchparallel mantle flow due to trench-roll back (Russo and Silver, 1994;Long and Silver, 2008;Long and Silver, 2009); (2) Type-B CPO of olivine (Jung and Karato, 2001;Kneller et al, 2005;Jung et al, 2006;Katayama and Karato, 2006;Kneller and van Keken, 2007;Karato et al, 2008); (3) the 3-D mantle flow around the slab Capitanio, 2012, 2013;Li et al, 2014; et al, 2017); (4) fault or crack-induced anisotropy in the slab (Faccenda et al, 2008;Healy et al, 2009); (5) strong radial anisotropy Kawakatsu, 2012, 2013); (6) CPO of serpentine in the slab-mantle interface and in the mantle wedge (Katayama et al, 2009;Jung, 2011;Nagaya et al, 2016); and (7) CPOs of chlorite (Kim and Jung, 2015;Kang and Jung, submitted) and amphibole in the lower part of mantle wedge (Ko and Jung, 2015;Kang and Jung, submitted). Since olivine in the mantle wedge is hydrated by the fluids from the dehydration of minerals in the subducting slab (Peacock and Hyndman, 1999;van Keken et al, 2011), and the stress is high in a collision zone in the subduction zones, it is highly likely that Type-B CPO of olivine is formed in the mantle wedge.…”
Section: Geophysical Implicationsmentioning
confidence: 99%
“…and (Table 2); their CPOs are important for interpreting seismic anisotropy in many subduction zones (Katayama et al, 2009;Jung, 2011;Brownlee et al, 2013;Morales et al, 2013;Kim and Jung, 2015;Ko and Jung, 2015;Nagaya et al, 2016;Kang and Jung, submitted). In addition, one of the important minerals in the middle and lower crust is amphibole, which is also elastically anisotropic (Aleksandrov and Ryzhova, 1961a;Siegesmund et al, 1989;Weiss et al, 1999;Kaczmarek and Tommasi, 2011;Lloyd et al, 2011;Ji et al, 2013;Ko and Jung, 2015;Brown and Abramson, 2016;Almqvist and Mainprice, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Gerya et al 2002;Gorczyk et al 2006Gorczyk et al , 2007Yamato et al 2007;Ernst & Liou 2008;Agard et al 2009;Meda et al 2010;Roda et al 2010Roda et al , 2012Le Voci et al 2014). In ocean-continent sub-Q3 Q4 duction systems, low viscosity hydrated mantle facilitates the exhumation and underplating of subducted oceanic and continental material at the base of the crust of the upper plate (Billen & Gurnis 2001;Hirth & Kohlstedt 2003;Billen 2008;Hirth & Guillot 2013;Nagaya et al 2016). When hydration is not considered, a dry and stiff mantle buttress characterizes the wedge area and strongly affects the thermomechanical regime during the subduction stage and subsequent continental collision (Marotta & Spalla 2007;Spalla & Marotta 2007;Gerya et al 2008;Meda et al 2010).…”
Section: Introductionmentioning
confidence: 99%